Modal frequency and shape curvature as a measure of implant fixation: A computer study on the acetabular cup. (October 2018) - Henyš, Petr; Leuridan, Steven; Goossens, Quentin; Mulier, Michiel; Pastrav, Leonard; Desmet, Wim; Sloten, Jos Vander; Denis, Kathleen; Čapek, Lukáš
Highlights: Natural frequencies are sensitive to a bone-implant shared contact area. Modal shapes need to be measured in order to track the natural frequencies. Curvature of modal shapes has a great potential as a fixation indicator. Abstract: Modal parameters are often investigated in order to assess the initial fixation of an implant. Most of studies are focused on the natural frequencies and frequency response function. Usually the femoral stem is tested although the acetabular cup fixation is important as well. The results of implant stability assessment are inconsistent and seem to suggest that frequency as a stability indicator is not sufficiently sensitive. In this study the sensitivity of the modal properties to changes in the bone-implant interface was investigated with the help of the finite element method (FEM). A novel fixation index based on modal shape curvature was investigated as a potential measure of the implant fixation. Modal frequencies are sensitive to interface changes in some manner, but suffer from insensitivity to local changes at bone-implant interface. The sensitivity up to 44% of natural frequencies to stiffness change due insertion steps was observed. The tested damage indicators are able to detect localized small changes in peripheral stiffness (5% stiffness reduction) with 95% confidence under the noise up to 1%. The modal shapes and their curvatures have a great potential to be a robust fixation indicator.